Assessing the Importance of Design Through Product Archaeology - Ulrich, Karl T.; Pearson, Scott (Management Science, 1998)
This paper assesses the importance of design in determining product costs by measuring the variation in design performance among a set of competing design efforts. This assessment is completed for a set of functionally similar products in a single product category: automatic drip coffee makers. The approach of this study is to measure the manufacturing content—the attributes of the design that drive cost—through analysis of the physical products themselves, and to estimate how variation in manufacturing content relates to variation in cost in a hypothetical manufacturing setting. We call this approach product archaeology. For the domain of coffee makers, we find significant variation in manufacturing content. This variation in manufacturing content corresponds to a range of estimated manufacturing costs, for a hypothetical manufacturing system, of approximately 50 percent of the average manufacturing cost of the products. We also find that differences in capabilities among product development efforts are the most plausible explanation for the differences in manufacturing content.